Epilepsyalarm: Desarrollo De Una Aplicación Móvil Para La Gestión Y Envío De Alertas Previo A Un Ataque De Epilepsia (2023)
Epilepsy is a fairly complex health problem to deal with, which affects bothmen and women of all ages, causing an alteration in the activity of thenerve cells and causing helplessness in critical situations that arise due to their medical condition. This disease causes involuntary seizures in the person whosuffers, and when an episode of these happens, the victim is left vulnerable.